Rapidly achieving a reliable full-ceramic interface of ZrC-SiC composite using Ti interlayer via pulsed electric current joining. Issue 5 (May 2023) - Lin, Jincheng; Zhou, Jiafeng; Zhang, Shuye; Lu, Fugang; Zhao, Jiaqi; Pan, Yucheng; Huang, Yongde; Lin, Panpan; He, Peng; Lin, Tiesong; Zhuang, Yanli
Abstract: A reliable full-ceramic interface of ZrC-SiC composite was achieved rapidly at low temperature via pulsed electric current joining. Using a Ti foil as joining interlayer, the Zr and Si atoms reacted with Ti to form Ti3 Zr3 Si3, while the dissolved C precipitated in form of TiC. The current delivering during joining promoted the atomic diffusion and caused the preferential growth of TiC, rapidly achieving a full-ceramic interface at 1300 ℃. Evaluating the reliability by Weibull distribution, the full-ceramic interface exhibited a considerable characteristic strength of 178 MPa, and its reliability was better than the raw ZrC-SiC composite. The in-situ formed ceramic interface toughened the joint via the mechanism of multi-cracking, crack deflection and termination. The proposed method provides a practical technology for the rapid joining of ultra-high temperature composites or the construction of layered composites with high toughness at low temperature. Highlights: A full-ceramic interface of ZrC-SiC composite was achieved rapidly using Ti interlayer. The full-ceramic interface exhibited a better reliability than the raw composites. Pulsed electric current promoted the atomic diffusion and induced preferential growth of TiC. The toughening mechanism for various interface was revealed.